Multiobjective optimization for performance-based seismic design of steel moment frame structures. - Liu, Min (Earthquake engineering & structural dynamics.)
The performance based seismic design of steel special moment resisting frame (SMRF) structures is formulated as a multiobjective optimization problem, in which conflicting design criteria that respectively reflect the present capital investment and the future seismic risk are treated simultaneously as separate objectives other than stringent constraints. Specifically, the initial construction expenses are accounted for by the steel material weight as well as by the number of different standard steel section types, the latter roughly quantifying the degree of design complexity related additional construction cost; the seismic risk is considered in terms of maximum interstory drift demands at two hazard levels with exceedance probabilities being 50 percent and 2 percent in 50 years, respectively. The present formulation allows structural engineers to find an optimized design solution by explicitly striving for a desirable compromise between the initial investment and seismic performance. Member sizing for code compliant design of a planar five story four bay SMRF is presented as an application example using the proposed procedure that is automated by a multiobjective genetic algorithm.